Food security in Food & Beverage sector - Demet Kocatepe (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2017)
The education level of people throughout the world increases food safety awareness is also increasing. In tourism sector, the investments to food security is increasing and applied to a variety of educational activities. Every year there are many food poisoning cases resulting and a part of in death in the world. Such serious incidents were observed in facilities such as hotels specifically catering service provided leads to both prestige and economic losses. In this study the cases of food poisoning occurred throughout the world and are given information about their effects on the tourism industry.